Sustainable Heritage Tourism in Urban Settings: Evaluating Glodok Chinatown’s of Jakarta Tourism Carrying Capacity - Nugroho, Fajar Aditya; Utami, Heryanti; Silvia; Hadi, M. Fiqri Haikal; Rata, Jeiel Offenedius Revinius (Politeknik Negeri Bali, 2025)
Urban heritage tourism increasingly contributes to cultural preservation and sustainable urban development, yet destinations in dense metropolitan settings often face acute pressure from rising visitation. This study evaluates the tourism carrying capacity of Glodok Chinatown, Jakarta’s oldest Chinese heritage district, by assessing its physical, socio-cultural, economic, environmental, and managerial components. Using a qualitative exploratory approach supported by field observations, regulatory review, and interviews with local residents, business actors, heritage experts, and government officials, the study provides a multidimensional analysis of capacity constraints. Results indicate considerable disparities between potential and reality. While the area’s Physical Carrying Capacity (PCC) and Real Carrying Capacity (RCC) remain structurally limited by narrow streets, mixed-use density, and constrained public spaces, the Effective Carrying Capacity (ECC) is found to be only 104 visitors per day. In contrast, actual visitation reaches 1,000–1,500 tourists on regular days, with spikes of over 5,000 visitors during major cultural festivals. This excess contributes to congestion, increased waste accumulation, deterioration of heritage structures, reduced walkability, and commercialization of cultural practices. Socio-economically, tourism benefits remain unevenly distributed, with small local MSMEs facing competition from larger commercial actors. Managerially, fragmented governance, sectoral decision-making, and the absence of an integrated heritage management entity hinder sustainable development efforts. The findings underscore the need for capacity-based planning through zoning, visitor flow redistribution, improved interpretation systems, and strengthened community participation to ensure Glodok’s cultural authenticity and long-term resilience.